Multi-biological activity assessment and phytochemical characterization of an aqueous extract of the Cymbopogon citratus grown in Palestine - Belal Rahhal; Mohammad Qneibi; Nidal Jaradat; Mohammed Hawash; Mohammad Qadi; Linda Issa; Sosana Bdir (BMC, 2024)
Abstract Background Plants have historically been a rich source of medicinal compounds, with many modern pharmaceuticals derived from botanical origins. In contemporary healthcare, there is a resurgence in utilizing botanical substances as recognized medicinal agents. This study delved into understanding the phytochemical makeup and the multifaceted biological activities of an aqueous extract from Cymbopogon citratus (C. citratus). The investigated activities were its effect on AMPA receptors, antioxidant capacity, anti-lipase, anti-α-amylase actions, cytotoxicity, and antimicrobial properties. Methods The extract of C. citratus received a comprehensive investigation, which included the study of its phytochemical composition, assessment of its antioxidant and anti-lipase properties, evaluation of its capacity to inhibit α-amylase, analysis of its impact on cell viability, and assessment of its antimicrobial activity. The approaches are used to clarify the complex physiological and biochemical characteristics. Results The results were compelling; receptor kinetics had a marked impact, notably on the GluA2 subunit. Regarding its medicinal potential, the extract demonstrated potent antioxidant and anti-diabetic activities with IC50 values of 15.13 and 101.14 µg/mL, respectively. Additionally, it displayed significant inhibitory effects on the lipase enzyme and showed cytotoxicity against the Hep3B cancer cell line, with IC50 values of 144.35 and 148.37 µg/mL. In contrast, its effects on the normal LX-2 cell line were minimal, indicating selectivity. Conclusion The aqueous extract of C. citratus shows promising therapeutic properties. The findings advocate for further research into its compounds for potential isolation, purification, and in-depth pharmacological studies, especially in areas like nervous system disorders, diabetes, obesity, and combating oxidative stress.